Modulating adsorbed hydrogen drives electrochemical CO2-to-C2 products - Feng, Jiaqi; Zhang, Libing; Liu, Shoujie; Xu, Liang; Ma, Xiaodong; Tan, Xingxing; Wu, Limin; Qian, Qingli; Wu, Tianbin; Zhang, Jianling; Sun, Xiaofu; Han, Buxing (Nature communications, 2023)
Electrocatalytic CO 2 reduction is a typical reaction involving two reactants (CO 2 and H 2 O). However, the role of H 2 O dissociation, which provides active *H species to multiple protonation steps, is usually overlooked. Herein, we construct a dual-active sites catalyst comprising atomic Cu sites and Cu nanoparticles supported on N-doped carbon matrix. Efficient electrosynthesis of multi-carbon products is achieved with Faradaic efficiency approaching 75.4% with a partial current density of 289.2 mA cm −2 at −0.6 V. Experimental and theoretical studies reveal that Cu nanoparticles facilitate the C-C coupling step through *CHO dimerization, while the atomic Cu sites boost H 2 O dissociation to form *H. The generated *H migrate to Cu nanoparticles and modulate the *H coverage on Cu NPs, and thus promote *CO-to-*CHO. The dual-active sites effect of Cu single-sites and Cu nanoparticles gives rise to the catalytic performance. A dual-site catalyst consisting of Cu nanoparticles (NPs) and atomic Cu sites is designed. The atomic Cu boosts H2O dissociation for modulating the *H coverage on Cu NPs, improving the efficiency of CO2 electroreduction to multi-carbon products.